Streptomyces sp. UKMCC_PT15: Potential anticancer agent producer - Zainal Abidin, Zaima Azira; Usup, Gires; Ahmad, Asmat; Lu, Chung-Kuang (2009)
The potential of Streptomyces sp. UKMCC-PT15 that was isolated from the gut of a sea cucumber from Pulau Tinggi, Johor as an anticancer agent producer was investigated. The isolate was able to tolerate up to 12% salt concentration and temperature of up to 45oC. Both polyketide synthase type I (PKS-I) and non-ribosomal peptide syntethases (NRPS) genes that are important in the biosyntheisi of secondary metabolites were present in this isolate. Molecular identification was also performed using 16S rDNA partial sequencing. A crude methanolic extract of this isolate was fractionated using flash column chromatography producing 10 fractions (ZAI1-20-1 – ZAI1-20-10). Fraction 4 (ZAI1-20-4) was then chosen for a further separation step using Sephadex LH-20. A total of 4 fractions were obtained (ZAI1-23-2 –ZAI1-23-4). Cytotoxicity test results against DLD-1 and CCRF-CEM cell lines showed that 5 fractions namely ZAI1-20-1, ZAI1-20-5, ZAI1-20-6, ZAI1-23-2 AND ZAI1-23-4 have the anticancer properties. Fraction 2 (ZAI1-23-2) was selected for further separation using HPLC using a photodiode array detector in the wavelength range 200-800nm on a C18, 5um column. A mobile phase comprising methanol:0.1% acetic acid (95:5) with a flowrate of 1ml/min was the best condition to separate ZAI1-23-2 to 5 fractions (ZAI1-29-1 – ZAI1-29-5). All the fractions were subjected to NMR and it was found that ZAI1-29-1 was successfully purified using HPLC.